TEKNOLOGI MAKLUMAT DAN KOMUNIKASI (ICT) DALAM PENGAJARAN DAN PEMBELAJARAN SAINS (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract This concept paper discussed about the importance of information and communication technology (ICT) integration in science teaching and learning concept. Nowadays telecommunication and multimedia technology has been used globally and this revolution has seeped into all sectors of society. With overall utilization of information technology, it can help to increase students level in order to get the information effectively. The ICT utilization in in teaching and learning process, the advantages of ICT and the implication to students and teachers were being discussed. The ICT also has disadvantages even though there are many advantages and big changes in educational field have been made. This discussion also highlighted the improvements to develop professionalism in education by providing many programs to increase their knowledge in ICT, teachers role as facilitator to students and the role of schools leader as a role model to objectify the ICT in educational field.Keyword : Information and Communication Technology, teaching and learning